Prevalens, viral load and types diversity of high-risk HPV in patients with infl ammatory and tumor diseases - T. A. Zykova; G. A. Nerodo; O. A. Bogomolova; M. N. Duritskiy; V. A. Sustretov; V. P. Nikitina; A. P. Menshenina; A. N. Shevchenko; I. A. Khomutenko; P. A. Kruze; E. V. Philatova (Медицинский вестник Юга России, 2018)
Objective: analysis of the type-specific prevalence of high-risk HPV in dependence on gender, age, the presence of cancer. Material and methods: 424 patients of the RRIO were examined. Urogenital smears in women and in men, urine in men were tested for HPV DNA using PCR. Results: The relative share of HPV-positive patients was 34.4% in women and 39.9% in men. The percentage of HPV-positive patients decreased in older women and increased in men. HPV was registered more oft en in women younger than 25 and older than 45 years old and in men aged 26-45 years. Multiple-type HPV infection was registered more oft en in young patients. HPV 16 was the most prevalent in men and women; next most prevalent types were HPV 31, 52, 18 and 56 in women and HPV 52, 56, 45 and 18 in men. HPV 51 was found in women only. HPV infections were registered in cancer patients 1.9 times more oft en than in patients with inflammatory diseases. A high viral load prevailed in women with cancer; viral load with varying clinical significance was equally frequent in patients with inflammatory diseases. Combinations of simultaneous infection with HPV and STI agents in women with cancer amounted to 70.6% of the total number of STI-positive patients and 41.5% in women with inflammatory diseases, in men – 66.7% and 38.1%, respectively. Conclusions: The obtained results allowed to reveal gender and age differences in the HPV prevalence in dependence on gender, age and the presence of cancer.